2018
DOI: 10.1007/s11517-018-1860-x
|View full text |Cite
|
Sign up to set email alerts
|

Nonparametric dynamical model of cardiorespiratory responses at the onset and offset of treadmill exercises

Abstract: This paper applies a nonparametric modelling method with kernel-based regularization to estimate the carbon dioxide production during jogging exercises. The kernel selection and regularization strategies have been discussed; several commonly used kernels are compared regarding the goodness-of-fit, sensitivity, and stability. Based on that, the most appropriate kernel is then selected for the construction of the regularization term. Both the onset and offset of the jogging exercises are investigated. We compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In previous research, the first-order system was proposed for V O 2 estimation during the single onset or offset period experiment [11] [33] [34]. However, the first-order system is not suitable when the input and output of the system become complicated as in our experiment.…”
Section: Discussionmentioning
confidence: 94%
“…In previous research, the first-order system was proposed for V O 2 estimation during the single onset or offset period experiment [11] [33] [34]. However, the first-order system is not suitable when the input and output of the system become complicated as in our experiment.…”
Section: Discussionmentioning
confidence: 94%
“…In the numerical simulation part for parameter selecting, we acquired the β value under the assumption that the system is a first-order system based on the previous study [20]. Our previous study [9] also revealed that in the single ascending or descending period, the system is close to a first-order system, but there are still exceptions because of the individual difference. However, in this research, the physiological information contains two periods of ascending (0 − 3 − 8km/h) or a full period with ascending and descending (3 − 8 − 3km/h).…”
Section: Resultsmentioning
confidence: 99%
“…Based on our previous work [9], the Stable Spline (SS) kernel which is shown in Eq. 7, demonstrates a better performance than the other kernels based on the aspects of accuracy, sensitivity, stability and smoothness.…”
Section: A Non-parametric Modeling Of Finite Impulse Response Based mentioning
confidence: 99%
See 1 more Smart Citation